THE EFFECTIVENESS OF INDONESIAN NATIONAL POLICE FUNCTION ON BANGGAI REGENCY POLICE INVESTIGATION (Investigation Case Study Year 2008-2016) - Hardianto Djanggih; Kamri Ahmad (Jurnal Dinamika Hukum, 2017)
Criminal justice processes are frequently unwell-implemented due to various investigators’ shortcomings in performing their function. This research aims to determine and analyze the effectiveness of the police investigation into the handling of Criminal Offenses in Banggai. This research employed socio-juridical methods approach particularly descriptive analytical research. The data analysis was conducted by descriptive qualitative and quantitative analysis. The results showed that: there is an imbalance between investigators and number of crimes; 70% of suspects were arrested by investigators without warrant; discrimination among suspects in investigation process occurs; investigators would prefer interrogating suspect without being assisted by lawyer; limited information given by the investigators to suspect’s family; suspects were detained without according to the applicable law and regulations.Keywords: effectiveness, police, investigation process